Fichte studies - Novalis 1772-1801 (Cambridge University Press, 2003)
This volume presents the first complete translation of Fichte Studies, a powerful, creative and sustained critique of Fichtean philosophy by the young philosopher-poet Friedrich von Hardenberg, who under the pen-name Novalis went on to become the most well-known and beloved of the early German Romantic writers. Anyone interested in the fate of German philosophy and literature immediately after Kant will find this collection of notes and aphorisms a treasure-trove of original contributions on the nature of self-consciousness, the relation of art to philosophy, and the nature of philosophical inquiry. There are also the beginnings of a strikingly contemporary-sounding semiotic theory. The text is translated by Jane Kneller, who also provides an introduction situating the Fichte Studies in the context of Novalis' life and work
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Fichte, Johann Gottlieb / 1762-1814; Fichte, Johann Gottlieb / 1762-1814 / Grundlage der gesamten Wissenschaftslehre; Fichte, Johann Gottlieb -- 1762-1814; Novalis -- 1772-1801